A COMPARATIVE STUDY ON NONLINEAR MODELING OF COUPLING BEAMS AS FRAME ELEMENT AND WALL ELEMENT USING PERFORM-3D - Batara, Ismail
The emergence of performance-based designs emphasizes nonlinear modeling of structural elements in order to describe the inelastic behavior of structures globally and the level of damage to structural elements during the seismic response. For example, in a coupled wall system, the coupling beam is the main dissipator of seismic forces. So, in assuming the nonlinear modeling of the coupling beam elements, it is need to be carefully considered and modeled appropriately. In using the PERFROM-3D nonlinear analysis computer program, several nonlinear approach models can be used, namely frame elements using nonlinear plastic hinge models and fiber sections (fiber hinges) then wall elements using nonlinear fiber-shell elements and fiber-shell models with additional truss, element to represent the diagonal reinforcement of the coupling beam. The four beam modeling approaches are used in this study, which gained a better understanding of the characteristics and behavior of the coupling beam and helped the user to choose the right model to perform the analysis of the nonlinear coupling beam. Based on nonlinear pushover analysis and time history analysis, it was found that the level of performance and structural response including the pushover capacity curve, roof displacement, base shear, total displacement and story drift of the four approach models are relatively the same as a whole. but based on the level of damage to the coupling beam elements there is a significant difference. The biggest damage occurred in the plastic hinge model, which is 0.48 LS and the fiber section model is 0.48 LS, then the fiber-shell element model is 0.40 LS and the smallest damage occurred in the fiber-shell + truss element, which is 0.1 LS. Based on the performance level, the frame element model provides a conservative performance and can be concluded as the best and most accurate model.